PENGARUH PELATIHAN KESEHATAN JIWA PADA TENAGA KESEHATAN TERHADAP PENGETAHUAN DAN KOLABORASI PELAYANAN KESEHATAN JIWA DI PUSKESMAS KOTA YOGYAKARTA - , Susi Rutmalem Bangun, Prof. Dr. dr. H. Soewadi, MPH, SpKJ(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Based on data from the Ministry of Health , the number of people with severe mental illness in Indonesia reached approximately one million more , or about 0.46 % . A total of 31 168 residents of Yogyakarta mentally ill . \" The number of people who experience mental illness in Yogyakarta is quite high . Figures estimate of 0.5 % of the total population in town